Contemporary Issues in Information Systems A Global Perspective - Reilly, Denis (IntechOpen, 2022)
Information technology (IT) and information systems (IS) are crucial to our everyday lives. This book brings together a collection of research papers related to the application of IT and IS to address issues at national levels.The first section provides some introductory material relating to IS and future challenges facing IS. The second section considers several diverse applications of IT and IS, ranging from Internet voting to missing person investigations.This volume is suitable for both academics and IT practitioners working in the industry, government, or service-providing sectors.